Ser mais para e com os demais: espiritualidade inaciana para autoconhecimento e projeto de vida de universitários. - Jesus, João Elton de (2021)
The present work aims to investigate how Ignatian spirituality can be an instrument to help university students in their self-knowledge and life project construction processes. To this end, we seek to understand the contemporary context, especially with regard to youth realities and the university world, with the reflections of Bauman, Baudrillard and Debord, who present their theories of liquid society, consumer society and society of the spectacle, and we go deeper into the youth realities, mainly with regard to work, education and spirituality. Having made this “photograph” about youth, object of this study, we present Ignatian sources such as the autobiography of Saint Ignatius, the founding documents of the Society of Jesus that are the basis for the structuring of what we call the Educational Apostolate, seeking to understand what is intended with it in the sense of monitoring and integral training of its students, especially those in higher education. Then, we identified, within the Jesuit and Ignatian framework, some lights to help in the process of integration and self-knowledge of university students, helping them to reconcile with their past, recognizing the potentialities and possibilities of action of their present; knowing themselves and the world they are in, so that they can project life, based on what each one is, their place of announcement, and also the meaning and purpose of their life and the values that guide their actions. We end, therefore, with the presentation of the “maintenance” of this life project, in a constant examination and evaluation, so that this student, in his autonomy and in the course of his life, can adapt to the constant demands and changes in the contemporary world, never losing sight of its principle and foundation and the main mission of being a person with and for others and in constant search for Magis and reconciliation with oneself, with others, with society, with the transcendent and with the common home.